Genetic evaluation of breeding efficiency estimated by Tomar ‎equation in Holstein cattle - Al-Samarai, F.R. (The Iraqi Journal of Veterinary Medicine, 2007)
Data analyzed included 13838 records belonged to 4100 Holstein cows over period 1988 to 2005, at the Nasr Dairy Cattle Station. The aim of the study is to evaluate sires genetically according to their daughters breeding efficiency which was estimated by Tomar equation and to estimate heritability and phenotypic trend for breeding efficiency.General Linear Model within SAS program was used to investigate the effect of some fixed factors on the breeding efficiency. The overall breeding efficiency ratio was 79.91% .Component of variance for random effects was estimated by MIVQUE method. Heritability of breeding efficiency was 0.08, whereas phenotypic trend for the same trait was positive and significant (P < 0.01), being 0.07%/year.The maximum and minimum BLUP estimates for 79 sires were 8.43% and 11.84%respectively.